PHYTOCHEMICAL PROFILE OF AZADIRACHTA INDICA: A COMPREHENSIVE REVIEW (International Journal of Food and Nutritional Sciences, 2022)
Azadirachta indica, commonly known as neem, is a tree with a rich history of medicinal use in various cultures, particularly in Ayurveda. This comprehensive review delves into the phytochemical profile of Azadirachta indica, highlighting its vast array of bioactive compounds and their therapeutic potential. Neem is renowned for its diverse range of phytochemicals, including terpenoids, flavonoids, polyphenols, and alkaloids. Key constituents such as azadirachtin, nimbin, quercetin, and nimbolide have been extensively studied for their medicinal properties. The review summarizes current research on the biological activities of these phytochemicals, which exhibit antimicrobial, anti-inflammatory, antimalarial, anticancer, and antioxidant effects. Azadirachtin, a prominent limonoid, is particularly noted for its potent insecticidal properties and role in integrated pest management. Flavonoids and polyphenols contribute significantly to neem's antioxidant capacity, providing protective effects against oxidative stress and associated diseases. The therapeutic applications of neem extend to skin disorders, diabetes management, and oral health, among others. Furthermore, the review addresses the pharmacokinetics, safety, and efficacy of neem extracts and isolated compounds, underscoring their potential as natural alternatives in pharmacotherapy. This comprehensive review aims to consolidate the vast amount of scientific data on Azadirachta indica, offering a detailed overview of its phytochemical richness and multifaceted benefits. By elucidating the mechanisms underlying its bioactivity, this review underscores the importance of neem in traditional medicine and modern pharmacological research, paving the way for future studies and potential clinical applications.